The Effectiveness of Problem-Based Learning in Improving Students Scientific Literacy Skills and Scientific Attitudes - Miranti Diah Prastika; Mustika Wati; Suyidno Suyidno (Universitas Lambung Mangkurat, 2019)
Scientific literacy skill is a key factor for overcoming real-life problems, but scientific literacy learning in schools has not been well trained. Therefore, the purpose of this study is to analyze the effectiveness of Problem Based Learning (PBL) in improving students scientific literacy skills and scientific attitudes. This research was part of research and development, with the Dick & Carey model. The research trial used one group pre-test and post-test design on 29 students of XI IPA 1 class in SMAN 5 Banjarmasin. The instruments of data collection were a scientific literacy test and scientific attitude questionnaires. Data were analyzed by the n-gain equation. The results showed that the n-gain score of students scientific literacy and scientific attitudes were 0.55 and 0.57; it means the increase was in moderate criteria. Therefore, PBL is effective to improve students scientific literacy skills and scientific attitudes.